..a b c为正,求证a^2/(b+c)+b^2/(c+a)+c^2/(a+b)>=1/2(a+b+c)
1个回答
a^2/(b+c)+b^2/(c+a)+c^2/(a+b)
大于
a^2/(a+b+c)+b^2/(b+c+a)+c^2/(c+a+b)
它等于
(a^2+b^2+c^2)/(a+b+c)
相关问题
a b c 为正实数,求证a/(a+2b+c)+b/(a+b+2c)+c/(2a+b+c)>=3/4
求证(a+b)/2c+(b+c)/2a+(a+c)/2b>=2c/(a+b)+2a/(b+c)+2b/(a+c)
a,b,c是正实数,求证√a^2+b^2+√b^2+c^2+√c^2+a^2>=√2*(a+b+c)
已知a,b,c为正实数,a+b+c=3求证:(a-c)^2/a+(b-a)^2/b+(c-b)^2/c≥(4/3)*(a
a>b>c,求证b^c2+c^a2+a^b2>b2^c+c2^a+a2^b
已知a,b,c都是正实数,求证(1)a2b≥2a−b,(2)a2b+b2c+c2a≥a+b+c.
求证:a2/b+b2/c+c2/a>_a+b+c(a\b\c均为正数)
设a,b,c是正实数,求证:1/2a+1/2b+1/2c≥1/(b+c)+1/(c+a)+1/(a+b).
若a,b,c属于正实数,求证:1/2a+1/2b+1/2c≥1/(b+c)+1/(a+c)+1/(a+b)
已知a>b>c>0,求证a^(2a)b^(2b)c^(2c)>a^(b+c)b^(a+c)c^(a+b)